First Case of Chryseobacterium gleum Post-COVID-19 in a Child with Recurrent Fever - Manuela Colosimo; Filippo Luciani; Maria Novella Pullano; Diana Marisol Abrego-Guandique; Luca Gallelli (Reports)
Background and Clinical Significance: Chryseobacterium gleum is a Gram-negative opportunistic and emerging pathogen able to induce systemic manifestations (e.g., peritonitis, pneumonia, urinary tract infections, meningitis) in immunocompromised patients. No data on children have been published. Case Presentation: A 2-year-old child presented in the pediatric ambulatory room with recurrent fever, submandibular lymphadenopathy, and skin rash. Laboratory findings revealed the presence of microcytic anemia with an increase in c-reactive protein. Chest X-ray reported mild accentuation of the bronchial structure, especially on the right side and middle–lower zone. In the peripheral blood smear, anisopoikilocytosis and elliptical red cells were evident. Clinical evaluation revealed the presence of conjunctivitis and polymorphic erythema, hyperemic pharynx and tonsils, SPO2 99%, auscultation of the chest, harsh vesicular murmur all over the area, and some wheezing. Microbiological analysis of sputum and throat swabs revealed the presence of numerous colonies of Chryseobacterium gleum confirmed using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS score > 2.2). Conclusions: This is the first case of Chryseobacterium gleum post-COVID in a child. We suggest that a quick identification and an appropriate treatment represent the critical factors able to prevent the adverse outcomes related to C. gleum infection.